(untitled) (Malaysian Journal of Civil Engineering, 2018)
Corrosion of reinforcement is a worldwide problem that affects durability and integrity of reinforced concrete structures. Repairing deteriorated reinforced concrete structures at an advanced stage is very costly and time consuming. It is more advantageous if corrosion can be detected at an earlier stage so that some preventive measures can be carried out. Monitoring of reinforcement corrosion in concrete can be achieved by embedding corrosion sensor within the concrete cover. In this study, an Embedded Capacitor Sensor (ECS) was developed to evaluate corrosion activity in concrete specimen. ECS was embedded in the concrete and its function is to measure the corrosion potential (Ecorr) of reinforcement. Ecorr measured by ECS is a result of the accumulated positive and negative charges between the two ECS plates from the corrosion process. For actual testing, ECS was tied to the reinforcement and embedded in concrete specimens. It was then calibrated using standard portable sensor (Ag/AgCl reference electrode) by measuring Ecorr. The ECS measurement is proven reliable because the reading pattern was similar to what shown by standard portable sensor. For monitoring, the ECS also was tied to the reinforcement and embedded in concrete at two different depths (15 mm and 25 mm). The concrete specimens were contaminated with 5% NaCl by weight of cement and then immersed in 3.5% NaCl solutions at room temperature to speed up the corrosion process. From this research, it was found that Ecorr for 15 mm concrete cover is higher than 25 mm concrete cover. Thicker cover delay the penetration chloride ion and oxygen to the reinforcement. Eventually, the bars were found corroded from the broken specimens that confirmed the detection of corrosion activities as recorded by the sensors.